Characteristic of fly ash derived-zeolite and its catalytic performance for fast pyrolysis of Jatropha waste - Vichaphund, S (Environmental technology, 2014)
Fly ash from pulp and paper industries was used as a raw material for synthesizing zeolite catalyst. Main compositions of fly ash consisted of 41 wt%SiO2, 20 wt%Al2O3, 14 wt%CaO, and 8 wt% Fe2O3. High content of silica and alumina indicated that this fly ash has potential uses for zeolite synthesis. Fly ash was mixed with 1-3 M NaOH solution. Sodium silicate acting as silica source was added into the solution to obtain the initial SiO2/Al2O3 molar ratio of 23.9. The mixtures were then crystallized at 160 degrees C for 24 and 72 h. Zeolites synthesized after a long synthesis time of 72 h showed superior properties in terms of high crystallinity, less impurity, and small particle size. The catalytic activities of fly ash-derived zeolites were investigated via fast pyrolysis of Jatropha wastes using analytical pyrolysis-gas chromatograph/mass spectrometer (GC/MS). Pyrolysis temperature was set at 500 degrees C with Jatropha wastes to catalyst ratio of 1:1, 1:5, and 1:10. Results showed that higher amounts of catalyst have a positive effect on enhancing aromatic hydrocarbons as well as decreasing in the oxygenated and N-containing compounds. Zeolite Socony Mobil-5 (ZSM-5) treated with 3 M NaOH at 72 h showed the highest hydrocarbon yield of 97.4%. The formation of hydrocarbon led to the high heating value of bio-oils. In addition, the presence of ZSM-5 derived from fly ash contributed to reduce the undesirable oxygenated compounds such as aldehydes, acids, and ketones which cause poor quality of bio-oil to only 0.8% while suppressed N-compounds to 1.7%. Overall, the ZSM-5 synthesized from fly ash proved to be an effective catalyst for catalytic fast pyrolysis application